EFFECT OF HEAT TREATMENT AND COMPOSITION VARIATIONS ON NI-20CR & WC-12CO COATINGS ON EROSION AND CORROSION RESISTANCE FOR MARINE APPLICATIONS - Gunawan Darma, Muhammad
316L stainless steel is prone to localised corrosion and erosion in seawater due to the potential degradation of its naturally formed protective oxide layer. The cause of this phenomenon can be attributed to the presence of aggressive media, specifically chloride ions, and the flow of current. One method used to prevent the oxidation of stainless steel is the application of a protective coating, such as the thermal spray process using high velocity oxygen – fuel (HVOF). The HVOF process utilises oxygen and propane gases to heat and deposit coating powder onto the substrate. Commonly utilised powders include Ni-20Cr and WC-12Co. Ni-20Cr exhibits favourable corrosion resistance, yet its efficacy in erosion resistance is compromised due to its relatively low hardness. WC-12Co exhibits high hardness, rendering it resistant to erosion. However, its corrosion resistance is compromised by galvanic corrosion resulting from the interaction between WC and Co. This study incorporated Ni-20Cr powder into WC-12Co compositions of 20% and 40%. The powder with a variable size obtained from meshing 400 was added to the composition, accounting for 40% of the total mixture. Furthermore, an additional parameter was introduced in post-heat powder coating treatment after spraying. This process, known as annealing, was conducted at a temperature of 700 °C for 2 hours. The hardness of the coating was assessed using microvickers. Solid particle erosion was used to test the resistance to erosion. Potentiodynamic polarisation is employed to assess corrosion resistance. The impact resistance was assessed through repeated drop ball falling tests. The inclusion of Ni-20Cr alloy results in a reduction in erosion resistance while simultaneously enhancing corrosion resistance. The lower hardness of Ni-20Cr compared to WC-12Co affects this, but it also increases corrosion resistance due to the formation of an oxide passive layer. Using 400 mesh increases resistance due to forming a less porous structure than other powder variations. The post-heat treatment process enhances erosion and corrosion resistance by promoting the formation of surface oxides. This inhibits the penetration of erosion particles and prevents contact between the coating and the corrosive environment. The repeated impact tests demonstrated strong adhesion bonds between the substrate and coating layers.